PEMANFAATAN MEDIA SOSIAL INSTAGRAM SEBAGAI PERSONAL BRANDING PADA MAHASISWA PRODI BISNIS DIGITAL UNIVERSITAS ABDURRAB PEKANBARU - Wahyuningsih, Endah (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
This research was conduction to find out how much social media Instagram is used personal branding among students of the Digital Departement study program at Abdurrab University, Pekanbaru. This research is quantitative research using survey methods. The sampling technique was incidental sampling of 9 respondents. Data processing uses SPSS for multiple linear regression analiysis. Based on research, the linear regression equation Y= 24,082+0,281X1+0,096X2 is obtained. The results obtained were that the independent valriable had no effect on the dependent variable, Instagram sosial media had no affect on personal branding. This was because the data obtained was small and there were other causes so that the results did not show an effect. Keywords :